2012
DOI: 10.1111/j.1538-7836.2012.04759.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study measuring the development of antibodies against platelet factor 4–heparin in healthy males after exposure to heparins

Abstract: To cite this article: Kelton JG, Warkentin TE, Moore JC, Arnold DM, Nazi I, Arepally GM, Roach JM, Fier I. A prospective study measuring the development of antibodies against platelet factor 4–heparin in healthy males after exposure to heparins. J Thromb Haemost 2012; 10: 1446–9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…We included heparin in our list of drugs, even though heparin‐induced thrombocytopenia (HIT) is associated with some unique features that distinguish it from classic DITP: HIT is associated with thrombosis rather than bleeding and the thrombocytopenia is typically less severe [18]. Heparin also provides illustrative exceptions to our DITP rules: for one, it has been associated with drug‐induced but not drug‐dependent antibodies in the syndrome of delayed‐onset HIT [19]; it may cause antibodies that bind to platelets in a drug‐dependent fashion without causing thrombocytopenia [20]; and because the pathologic heparin‐dependent antibodies are transient, a heparin re‐challenge only produces recurrent thrombocytopenia when administered in close proximity to an episode of HIT [21]. Nevertheless, because it has been proven to cause thrombocytopenia in many reports, heparin (which includes unfractionated heparin, low‐molecular‐weight heparins, polysulfated chondroitin sulphate and other glycosaminoglycans) was included in our list of DITP drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included heparin in our list of drugs, even though heparin‐induced thrombocytopenia (HIT) is associated with some unique features that distinguish it from classic DITP: HIT is associated with thrombosis rather than bleeding and the thrombocytopenia is typically less severe [18]. Heparin also provides illustrative exceptions to our DITP rules: for one, it has been associated with drug‐induced but not drug‐dependent antibodies in the syndrome of delayed‐onset HIT [19]; it may cause antibodies that bind to platelets in a drug‐dependent fashion without causing thrombocytopenia [20]; and because the pathologic heparin‐dependent antibodies are transient, a heparin re‐challenge only produces recurrent thrombocytopenia when administered in close proximity to an episode of HIT [21]. Nevertheless, because it has been proven to cause thrombocytopenia in many reports, heparin (which includes unfractionated heparin, low‐molecular‐weight heparins, polysulfated chondroitin sulphate and other glycosaminoglycans) was included in our list of DITP drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory criteria focused on the development of IgG antibodies binding to platelets, which is the most common mechanism of DITP; thus, our criteria would not capture antibodies that target megakaryocytes [24], complement-mediated thrombocytopenia and cell-mediated drug reactions. A fifth criterion may be considered for future prospective evaluations of DITP testing: the absence of antibody binding to platelets in individuals taking the drug who do not develop thrombocytopenia, as has been shown for heparin [20] and vancomycin [25]. Although the list we compiled represents those drugs with the strongest evidence for an association with DITP, such a list should be used with caution because other drugs should be considered in any patient with typical clinical features and a compatible temporal association.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…This model of immune sensitization has been demonstrated by studies reporting PF4 binding to bacterial surfaces are capable of binding anti‐PF4–heparin antibodies . In addition, some healthy individuals exposed to heparin in the absence of surgery also produce anti‐PF4–heparin antibodies . Zheng et al .…”
Section: Introductionmentioning
confidence: 86%
“…Thus, in contrast to other drug‐induced thrombocytopenias, HIT is additionally characterized by an increased risk of venous and arterial thrombosis, which can lead to devastating clinical outcomes in affected patients . Of note, PF4/heparin‐specific antibodies are also found in the general population, and it was recently demonstrated that heparin administration in healthy subjects without a history of HIT induces PF4/heparin antibody formation without a concomitant drop in platelet count or HIT …”
Section: Introductionmentioning
confidence: 99%